2022
DOI: 10.1073/pnas.2211326119
|View full text |Cite
|
Sign up to set email alerts
|

Wasteosomes ( corpora amylacea ) as a hallmark of chronic glymphatic insufficiency

Abstract: In different organs and tissues, the lymphatic system serves as a drainage system for interstitial fluid and is useful for removing substances that would otherwise accumulate in the interstitium. In the brain, which lacks lymphatic circulation, the drainage and cleaning function is performed by the glymphatic system, called so for its dependence on glial cells and its similar function to that of the lymphatic system. In the present article, we define glymphatic insufficiency as the inability of the glymphatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 152 publications
0
14
0
3
Order By: Relevance
“…For example, CA have been shown to contain ubiquitin, providing evidence that they may interact with the UPS, but more research is needed to elucidate their relationship ( Augé et al, 2018 ). Additionally, the glymphatic system may be associated with the extrusion of CA, since CA are thought to be a hallmark of chronic glymphatic insufficiency ( Riba et al, 2022b ). It is likely these waste clearance mechanisms work together to identify, sequester, and clean the brain from pathological debris, and in proteinopathies such as AD, their proper functioning is essential to prevent or delay disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, CA have been shown to contain ubiquitin, providing evidence that they may interact with the UPS, but more research is needed to elucidate their relationship ( Augé et al, 2018 ). Additionally, the glymphatic system may be associated with the extrusion of CA, since CA are thought to be a hallmark of chronic glymphatic insufficiency ( Riba et al, 2022b ). It is likely these waste clearance mechanisms work together to identify, sequester, and clean the brain from pathological debris, and in proteinopathies such as AD, their proper functioning is essential to prevent or delay disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to the clearance of tau through the glymphatic system is corpora amylacea (CA)-mediated waste clearance, a mechanism present in the central nervous system and other tissues. CA, also known as wasteosomes ( Riba et al, 2022a , b , 2023 ), have recently been linked to the glymphatic system ( Riba et al, 2022b ). CA are granular bodies ranging from 10 to 50 μm that accumulate waste products throughout the brain ( Cavanagh, 1999 ; Navarro et al, 2018 ; Riba et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although we found that these CA make up only 2 percent of its entire population in our brain stem samples, it is worth noting that certain vessels tend to accumulate CA throughout a long trajectory ( Figure 5D , Supplementary Figures 12 – 16 ). Riba et al ( 2022 ) recently suggested the accumulation of CA as a sign for failure the of glymphatic system to remove waste. According to this theory, accumulation of CA should occur predominantly in perivenous spaces rather than in periarterial spaces.…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of brain fluid transport may be a novel target for developing new drugs to fight acute and chronic inflammation in the brain. There is evidence that the presence of increased wasteosomes (or corpora amylacea i.e., amyloid bodies) is an indicator of chronic failure of the GS activity [ 151 ]. Chronic lymphatic insufficiency is a risk factor for NDDs, and thus, improvement of the GS is a novel target of AD drug strategies.…”
Section: Conventional and Novel Targets For Slowing And/or Preventing...mentioning
confidence: 99%